Malignant melanoma in children aged 0-12. Review of 289 cases of the literature. - Bonifazi, E.; Bilancia, M.; Berloco, A.; Ciampo, L.; De Roma, M.R. (European Journal of Pediatric Dermatology, 2001)
The rarity of prepubertal melanoma prevents a statistical evaluation of data and a comparison with the data of melanoma in adults. We tried to fill this gap by reviewing 289 cases published in the relevant literature of the last century. Although taking into account their understandable lacunas, these data allowed us to do some considerations. The distribution of cases per year in the first 12 years is uniform. The female is slightly more frequently -54.7%- affected by malignant melanoma as compared with the male even at this prepubertal age. The site distribution in the two sexes is different as compared with adults. In females the trunk is more frequently affected -41.56%- than in males -30.71%-. Moreover, the lower limb is almost equally affected in females -25.32%- and in males -26.77%-. The head is more significantly -27.76%- affected in the prepubertal age as compared with adults -16.63%-. The most important favoring factor at this age -present in one third of the cases- is congenital melanocytic nevus, especially the giant type. The number of died children is significantly affected by the presence of a giant congenital melanocytic nevus -70.15%-, whereas it is not influenced by the age and the sex -37.40% in males and 39.24% in females-. The number of died children is also influenced by the presence of adenopathy -63.40% versus 6.17% in cases without adenopathy-.